Reply to Comment on 'Exact solutions to the various nonlinear evolution equations' - Kaya, Dogan; Inan, Ibrahim E. (Iop Publishing Ltd, 2011)
A reply to the comment on our paper (Kaya and Inan 2009 Phys. Scr. 79 045005).